Double bond formation based on nitroaldol reaction and radical elimination: A prototype segment connection method for the total synthesis of nigricanoside A dimethyl ester. Issue 19 (9th May 2018) - Tsunoda, Takayuki; Fujiwara, Kenshu; Okamoto, Satoshi; Kondo, Yoshihiko; Akiba, Uichi; Ishigaki, Yusuke; Katoono, Ryo; Suzuki, Takanori
Graphical abstract: Highlights: A prototype segment connection method for the synthesis of nigricanoside A dimethyl ester. Olefination to give a double bond, which has an ether group at an allylic position. Olefination by nitroaldol reaction, chlorination or thionocarbonylation, and radical elimination. Abstract: During the course of our studies toward the total synthesis of nigricanoside A dimethyl ester, a prototype method for the connection of the left- and right-half segments at the C9′–C10′ double bond was developed using a model system. The method was based on a simple three-step process including: (i) a nitroaldol reaction, (ii) chlorination or thionocarbonylation, and (iii) radical elimination.